A Liquid Chromatography with Tandem Mass Spectrometry-Based Proteomic Analysis of the Proteins Secreted by Human Adipose-Derived Mesenchymal Stem Cells - Nakashima, Yoshiki (Cell Transplant, 2018)
Liquid chromatography using a tandem mass spectrometer (LC-MS/MS) is a method of proteomic analysis. A shotgun analysis by LC-MS/MS comprehensively identifies proteins from tissues and cells with high resolution. The hepatic function of mice with acute hepatitis following the intraperitoneal administration of CCL4 was improved by the tail vein administration of the culture conditional medium (CM) of human mesenchymal stem cells from adipose tissue (hMSC-AT). In this study, a secreted protein expression analysis of hMSC-AT was performed using LC-MS/MS; 128 proteins were identified. LC-MS/MS showed that 106 new functional proteins and 22 proteins (FINC, PAI1, POSTN, PGS2, TIMP1, AMPN, CFAH, VIME, PEDF, SPRC, LEG1, ITGBL, ENOA, CSPG2, CLUS, IBP4, IBP7, PGS1, IBP2, STC2, CTHR1, CD9) were previously reported in hMSC-AT-CMs. In addition, various proteins associated with growth (SAP, SEM7A, PTK7); immune system processes (CO1A2, CO1A1, CATB, TSP1, GAS6, PTX3, C1 S, SEM7A, G3P, PXDN, SRCRL, CD248, SPON2, ENPP2, CD109, CFAB, CATL1, MFAP5, MIF, CXCL5, ADAM9, CATK); and reproduction (MMP2, CATB, FBLN1, SAP, MFGM, GDN, CYTC) were identified in hMSC-AT-CMs. These results indicate that a comprehensive expression analysis of proteins by LC-MS/MS is useful for investigating new factors associated with cellular components, biological processes, and molecular functions.